PENGARUH PENERAPAN STRATEGI PEMBELAJARAN FIRE UP TERHADAP KEAKTIFAN BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DI MTS ROUDLOTUL ULUM KECAMATAN TANDUN KABUPATEN ROKAN HULU - Aswan Nur Hamzah; Gimin Gimin; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the effect of the FIRE UP learning strategy on student learning activeness in the eyes of PPKn in MTs Roudlotul Ulum, Tandun District, Rokan Hulu Regency. The formulation of the problem in this study is whether the use of the FIRE UP learning strategy affects student learning activeness in PPKn subjects in Roudlotul Ulum MTs, Tandun District, Rokan Hulu District. This research uses an experimental qualitative approach. The population in this study was grade VII students at Roudlotul Ulum MTs in Rokan Hulu district. The sample in this study was taken based on the